Biosynthesis of medium chain length alkanes for bio-aviation fuel by metabolic engineered Escherichia coli. (September 2017) - Wang, Meng; Nie, Kaili; Cao, Hao; Xu, Haijun; Fang, Yunming; Tan, Tianwei; Baeyens, Jan; Liu, Luo
Graphical abstract: Biosynthesis pathway for producing medium-chain alkanes. Highlights: Design of a novel process for bio-synthesis of aviation fuel. A plant origin FASs was introduced to improve the production of fatty acid. A chain length specific thioesterase was used to control the chain length of alkane. A heterologous ACP was used to improve the selectivity of introduced thioesterase. Abstract: The aim of this work was to study the synthesis of medium-chain length alkanes (MCLA), as bio-aviation product. To control the chain length of alkanes and increase the production of MCLA, Escherichia coli cells were engineered by incorporating (i) a chain length specific thioesterase from Umbellularia californica ( UC ), (ii) a plant origin acyl carrier protein (ACP) gene and (iii) the whole fatty acid synthesis system (FASs) from Jatropha curcas ( JC ). The genetic combination was designed to control the product spectrum towards optimum MCLA. Decanoic, lauric and myristic acid were produced at concentrations of 0.011, 0.093 and 1.657 mg/g, respectively. The concentration of final products nonane, undecane and tridecane were 0.00062 mg/g, 0.0052 mg/g, and 0.249 mg/g respectively. Thioesterase from UC controlled the fatty acid chain length in a range of 10–14 carbons and the ACP gene with whole FASs from JC significantly increased the production of MCLA.